Real-world experience of leadless left ventricular endocardial cardiac resynchronization therapy: A multicenter international registry of the WiSE-CRT pacing system - Sieniewicz, Benjamin J.; Betts, Timothy R.; James, Simon; Turley, Andrew; Butter, Christian; Seifert, Martin; Boersma, Lucas V.A.; Riahi, Sam; Neuzil, Petr; Biffi, Mauro; Diemberger, Igor; Vergara, Pasquale; et al. (Heart Rhythm, 2020)
Background: Biventricular endocardial pacing (BiV ENDO) is a therapy for heart failure patients who cannot receive transvenous epicardial cardiac resynchronization therapy (CRT) or have not responded adequately to CRT. BiV ENDO CRT can be delivered by a new wireless LV ENDO pacing system (WiSE-CRT system; EBR Systems, Sunnyvale, CA), without the requirement for lifelong anticoagulation. Objective: The purpose of this study was to assess the safety and efficacy of the WiSE-CRT system during real-world clinical use in an international registry. Methods: Data were prospectively collected from 14 centers implanting the WiSE-CRT system as part of the WiCS-LV Post Market Surveillance Registry. (ClinicalTrials.gov Identifier: NCT02610673). Results: Ninety patients from 14 European centers underwent implantation with the WiSE-CRT system. Patients were predominantly male, age 68.2 ± 10.5 years, left ventricular ejection fraction 30.6% ± 8.9%, mean QRS duration 180.7 ± 27.0 ms, and 40% with ischemic etiology. Successful implantation and delivery of BiV ENDO pacing was achieved in 94.4% of patients. Acute (<24 hours), 1- to 30-day, and 1- to 6-month complications rates were 4.4%, 18.8%, and 6.7%, respectively. Five deaths (5.6%) occurred within 6 months (3 procedure related). Seventy percent of patients had improvement in heart failure symptoms. Conclusion: BiV ENDO pacing with the WiSE-CRT system seems to be technically feasible, with a high success rate. Three procedural deaths occurred during the study. Procedural complications mandate adequate operator training and implantation at centers with immediately available cardiothoracic and vascular surgical support.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Cardiac resynchronization therapy; Endocardial pacing; Heart failure; Leadless pacing; Nonresponder